The End of Second Class - Nicol, Nancy (Canada : Nicol, Nancy, 2006)
The End of Second Class is a powerful documentary that traces the debate on same sex marriage in Canada up to the passage of equal marriage legislation on July 20, 2005. The story is told from the perspective of three couples from B.C., Ontario and Quebec and lawyers and activists who sought to uphold the Charter rights of lesbians and gay men. The End of Second Class vividly paints the context in which gays and lesbians fought to overcome a history of discrimination and second class status and sought to persuade both the courts and the Parliament of Canada to affirm their right to marry.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films